Autoantibodies Predicting Diabetes mellitus Type I in Celiac Disease - Galli-Tsinopoulou, A.; Nousia-Arvanitakis, S.; Dracoulacos, D.; Xefteri, M.; Karamouzis, M. (Hormone research, 1999)
Celiac disease (CD) and diabetes mellitus type I (DM-I) are both autoimmune diseases. Abnormal first-phase insulin response (FPIR) is associated with the prediabetic phase. Glutamic acid decarboxylase (GAD) and islet cell antibodies (ICAs) – especially the tyrosine phosphatase-like protein IA-2 antibodies – are considered to be serological markers of DM-I future development. The aim of this study is to investigate the presence of autoantibodies (GAD, IA-2) in individuals with CD, on a gluten-free diet, who have normal intestinal morphology. Thirty patients with CD (4–22, mean 15 years), 30 newly diagnosed diabetic children (2.5–16, mean 10 years) and 30 healthy subjects (7–35, mean 18 years) were investigated. Serum GAD and IA-2 autoantibodies were assessed by a quantitative enzyme-linked immunosorbent assay (ELISA) method in all patients and controls. Seven CD patients (23%), 28 diabetic children (93%) and none in the control group had positive GAD and IA-2 antibodies. The FPIR was normal in CD patients (≥46 mU/l). Conclusions: GAD and IA-2 antibodies are detected in 23% of patients with CD. These patients may be at risk to develop DM-I. Regular follow-up and determination of FPIR for the early diagnosis of the prediabetic phase in patients with CD having circulating autoantibodies is recommended.